Does Covid-19’s Influence on Commercial Banking Performance ? : Evidence from Indonesia - Nanik Kustiningsih; Ali Farhan; Parwita Setya Wardhani; Noneng R. Sukatmadiredja (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2022)
This article is intended to examine the effect of Covid-19 on financial performance in the banking industry represented by Bank BNI, Bank BRI, Bank CIMB Niaga, and Bank Mandiri with the variables Net Performing Loan, Loan to Deposit Ratio and Non Performing Loan as a measure of financial performance. The analysis used is the Mann Whitney test and the Kolmogrov Smirnov test. Based on the results of the different tests, it was found that; 1) Covid-19 has a negative but not significant effect on the net profit margin, 2) Covid-19 has a negative and significant effect on the loan to deposit ratio, and Covid-19 has a positive and significant effect on non-performing loans.